Targeting Secondary Hematoma Expansion in Spontaneous Intracerebral Hemorrhage – State of the Art - Guan, Jian; Hawryluk, Gregory W. J. (Frontiers in Neurology, 2016)
Spontaneous intracerebral hemorrhage (SICH), defined broadly as intracerebral hemorrhage not related to trauma, results in long-term disability or death in a large proportion of afflicted patients. Current management of this disease is predominantly supportive, including airway protection, optimization of hemodynamic parameters, and management of intracranial pressure. No active treatments that demonstrate beneficial effects on clinical outcome are currently available. Animal models of SICH have allowed for the elucidation of multiple pathways that may be attractive therapeutic targets. A minority of these, such as aggressive blood pressure management and recombinant activated factor VII administration, have led to large-scale clinical trials. There remains a critical need for further translational research in the realm of SICH.